TV ADVERTISEMENT AND SERVICES OF MOBILE PHONE COMPANIES: (Analytical Study of the Trends of Companies and the Public towards Television Advertisement) - Leith Abbas, Zeinab (ALBAHITH ALALAMI, 2022)
An advertisement is a human activity as old as human societies. As it was practiced by each society in accordance with the circumstances of the times and the means of communication available. The evolution of advertisement in the modern era reflected many factors to become an essential part of the lives of individuals in the world. Interesting in television advertising has increased in particular because it is the first and most influential mass media in the minds of people. Advertisements play a big role in our lives as individuals. As advertisements surround us where we have been found; and bring us many benefits; as well as their contribution to accelerate the process of economic development and the vital role of the means of communication as a source of funding. The importance of advertising influenced the increase in production and interest in the distribution of products on a large scale to be accessible to the consumer audience which necessitated attention to inform the consumer audience through advertisement. As the media is inherent to human life in this era, it has been necessary for researchers in the field of communication to pay enough attention after it became one of the basic functions of mass communication. In view of the television’s wide spread and its role as an advertising medium and its characteristics, this research dealt with the subject of (TV Advertisement and Services of Mobile Phone Companies: Analytical Study of the Trends of Companies and the Public towards Television Advertisement). Therefore, our research is significant to clarify many things that inevitably affect the significance of the oriented advertisement.